2019
DOI: 10.14260/jemds/2019/474
|View full text |Cite
|
Sign up to set email alerts
|

Uterovaginal Packing With Rolled Gauze in Post-Partum Haemorrhage, a Retrospective Study in Malda Medical College, West Bengal

Abstract: BACKGROUND Post-Partum Haemorrhage (PPH) is one of the five leading causes of maternal death in the developed and developing countries. PPH less than up to 1000 ml is well tolerated by a healthy pregnant woman particularly due to physiological increase in the plasma and the red cell mass during pregnancy. We wanted to determine efficacy of uterovaginal packing and its sequelae in low resource settings. METHODS After ethical committee permission and informed patient consent, a four-year retrospective study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…The efficacy of uterine packing depends upon its proper application and its employment early in the course of postpartum haemorrhage. Success rates reported in other studies were comparable to our study, 89.14% by Khairunnisa Nizam, 91.8 % by Malay et al and 90.09% by Javed et al 23,24,25 . Rashmi Bagga et al, reported two cases of, a primary and a secondary PPH, successfully managed with uterovaginal packing 26 .…”
Section: Resultssupporting
confidence: 90%
“…The efficacy of uterine packing depends upon its proper application and its employment early in the course of postpartum haemorrhage. Success rates reported in other studies were comparable to our study, 89.14% by Khairunnisa Nizam, 91.8 % by Malay et al and 90.09% by Javed et al 23,24,25 . Rashmi Bagga et al, reported two cases of, a primary and a secondary PPH, successfully managed with uterovaginal packing 26 .…”
Section: Resultssupporting
confidence: 90%
“…As far as efficacy is concerned it was noted to be effective in 88.8% of women. Success rate reported in other studies were comparable to our study 89.14% by Nizam et al 25 , 91.8% by Malay et al 26 and 90.09% by Javed et al 17 Bagga et al 27 reported 88.9% efficacy with Uterovaginal packing. In a study conducted by Dabelea et al 28 , postpartum hemorrhage was arrested in 90% of women with Uterovaginal packing and the result of our study stands consistent with the findings of this study in terms of efficacy.…”
Section: Resultssupporting
confidence: 89%
“…In other cases, patient is stabilized while preparing for surgery and sometimes surgery is not needed as the bleeding gets stopped with this conservative procedure. 7,8 We conducted this study to see the success of this procedure in low resource settings having a high rate of PPH. No studies have been conducted on this procedure in the recent years despite the fact that it is being frequently used to control PPH in tertiary care hospitals.…”
Section: Introduction Introductionmentioning
confidence: 99%